Diaspora by another name: the making of refugees in Cold War China - Jiaqi M. Liu; Clare Xiaoqian Wan (Comparative Migration Studies)
Abstract By examining China’s refugee policies from 1949 to 1982, this article demonstrates how the Chinese state redefined “return” and “refugee” to serve shifting political objectives. While China is often perceived as a source, rather than a host, of asylum seekers, it hosted over 320,000 displaced migrants—primarily ethnic Chinese from Southeast Asia—during the Cold War. Through a systematic discourse analysis of 382 People’s Daily articles, we identify four state narratives—diaspora, diplomatic tool, ideological sanctuary, and legal duty—that structured how China labeled displaced migrants, interpreted their sentiments, and determined their settlement. These models evolved dynamically: from the 1950s to the late 1970s, China framed displaced migrants as both diasporic returnees and victims of foreign persecution to bolster its legitimacy. During the Cultural Revolution, they were recast as Maoist returnees seeking ideological redemption. By 1978, the state invoked international legal norms by portraying them as “refugees” to secure global assistance amid the Indochinese refugee crisis. We argue that China’s refugee discourse functioned as a flexible political instrument that unsettled rigid distinctions between voluntary and forced migration. Our findings advance a constructivist understanding of migration categories and offer a historically grounded critique of refugee politics beyond Western-centric Cold War narratives.